2019
DOI: 10.3389/fgene.2019.01118
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Circulating Tumor DNA to Monitor and Predict Response to Treatment in Colorectal Cancer

Abstract: Background: Colorectal cancer is one of the most common cancers worldwide and has a high mortality rate following disease recurrence. Treatment efficacy is maximized by providing tailored cancer treatment, ideally involving surgical resection and personalized neoadjuvant and adjuvant therapies, including chemotherapy, radiotherapy and increasingly, targeted therapy. Early detection of recurrence or disease progression results in more treatable disease and is essential to improving survival outcomes. Recent adv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
59
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 72 publications
(68 citation statements)
references
References 131 publications
4
59
0
Order By: Relevance
“…Because earlier detection of CRC recurrence may facilitate potentially curable metastasectomy, the application of a more sensitive assay, such as one targeting hypermethylated BCAT1 and IKZF1 ctDNA, during surveillance might improve outcomes in recurrent CRC. Consistent with published data showing that methylation alterations to BCAT1 and IKZF1 can be identified in plasma well before radiographic recurrence (25,28,30,31,33), the current study demonstrated COLVERA positivity up to six months before imaging suggested recurrence. Nevertheless, without directly comparing results of regimented serial CEA and radiographic surveillance with serial ctDNA and radiographic surveillance, it is impossible to know whether application of ctDNA will lead to earlier radiographic detection and, most importantly, whether earlier radiographic detection will translate into improved cancer-related outcomes.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Because earlier detection of CRC recurrence may facilitate potentially curable metastasectomy, the application of a more sensitive assay, such as one targeting hypermethylated BCAT1 and IKZF1 ctDNA, during surveillance might improve outcomes in recurrent CRC. Consistent with published data showing that methylation alterations to BCAT1 and IKZF1 can be identified in plasma well before radiographic recurrence (25,28,30,31,33), the current study demonstrated COLVERA positivity up to six months before imaging suggested recurrence. Nevertheless, without directly comparing results of regimented serial CEA and radiographic surveillance with serial ctDNA and radiographic surveillance, it is impossible to know whether application of ctDNA will lead to earlier radiographic detection and, most importantly, whether earlier radiographic detection will translate into improved cancer-related outcomes.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with prior studies (28), the current study showed that the specificity of CEA in the 295 patients without cancer recurrence was higher than that of COLVERA. However, the significance of a false positive result in the current study is unclear due to the relatively short follow-up period.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The potential for liquid biopsy in guiding treatment and monitoring the disease is compelling and may soon be translated to clinical practice. In recent years, ctDNA has been shown to be a powerful tool in (1) assessing the adequacy of surgical tumor clearance and thereby the risk of recurrence (2) in selecting the most appropriate targeted therapy and (3) in following responses to systemic treatments [73,74]. The reappearance or increase in ctDNA, along with the emergence of new mutations, is associated with recurrence, progression and resistance to therapy.…”
Section: Liquid Biopsy: Ctdna and Tumor Mutation Burdenmentioning
confidence: 99%
“…Perineural invasion (PNI), high tumor budding and compromised surgical margin are also strong predictors of disease recurrence [3][4][5][6]. Circulating tumor DNA is a promising novel biomarker in colorectal cancer (CRC) and could be the most influential prognostic marker after radical surgery, but its predictive value has not yet been established [7][8][9].…”
Section: Introductionmentioning
confidence: 99%